2018
DOI: 10.1371/journal.pone.0195152
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of domestic violence experience among recently-married women residing in slums in Pune, India

Abstract: The high risk of experiencing domestic violence (DV) among married women in India who reside in slum communities underscores the need for effective, evidence-based, and culturally-tailored primary prevention. To inform such DV primary prevention strategies for this population, we herein aimed to identify correlates of DV experience in early marriage. Utilizing a cross-sectional design, potential correlates of DV experience were explored among a geographically-clustered random sample of 100 recently-married wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 31 publications
4
18
0
Order By: Relevance
“…Such findings reflect deep-rooted gender inequalities of Indian society. 7,14,29,30 This study found that women having dependable family support were less likely to experience DV than their counterparts, which is comparable with few other studies. 7,15 This suggests the role of programs aimed at strengthening the family cohesion and bonding.…”
Section: Discussionsupporting
confidence: 88%
“…Such findings reflect deep-rooted gender inequalities of Indian society. 7,14,29,30 This study found that women having dependable family support were less likely to experience DV than their counterparts, which is comparable with few other studies. 7,15 This suggests the role of programs aimed at strengthening the family cohesion and bonding.…”
Section: Discussionsupporting
confidence: 88%
“…These studies showed that the prevalence of women experiencing physical, psychological or sexual violence (inflicted by spouses) ranged from 17% to 59%. 8–13 National Family Health Survey-3 (NFHS-3, 2005–2006) had a domestic violence module which addresses the physical, emotional and sexual violence among women of reproductive age group. 14 It showed that nearly 35% of women experienced physical violence, 16% faced emotional violence and about 10% experienced sexual violence from their husband/partners.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on domestic violence in India have found high levels of normative acceptance of domestic violence (Jejeebhoy, 1998), and shown that tolerance of domestic violence in the community and justification of marital violence is associated with higher risk for perpetration of domestic violence (Begum et al, 2015; Kalokhe et al, 2018). Thus, intervening to interrupt and prevent domestic violence requires not only services for survivors and efforts to facilitate their empowerment at the individual level, but also shifts in community norms and facilitating the empowerment of community members who can effectively mobilize a community response to violence.…”
Section: Introductionmentioning
confidence: 99%